Safe-Haven and Diversification Roles of Gold and Bitcoin: Evidence from Financial Markets - Bayu Avrianto Raksakadarma; Raden Aswin Rahadi (Green Publisher Indonesia, 2025)
This study investigates the safe-haven and diversification roles of gold and Bitcoin in financial markets from 2015 to 2025. With rising economic uncertainties, the need for reliable safe-haven assets has become critical. Gold has historically provided stability during crises, whereas Bitcoin's volatile nature raises questions about its reliability as a safe haven. Through empirical analysis, including GARCH models and quantile regression, the research evaluates the performance of both assets during market stress. Findings indicate that gold consistently outperforms Bitcoin in terms of downside protection, confirming its status as a traditional safe-haven asset. Conversely, Bitcoin offers potential diversification benefits, enhancing portfolio performance when combined with gold. The results support the notion that integrating both assets can lead to improved risk-adjusted returns, making a dual-asset investment strategy a practical approach for investors navigating market uncertainties.